Transformational Model: Pela Communicative Action and Systemic Action: - Rahmat Saputra, Andhika; Zahra Azizah, Putri; Sari, Adilati (KARSA Journal of Social and Islamic Culture, 2021)
This study refers to how the Pela concept within the Maluku. This study relates to how the Pela concept within the Maluku community has a broad influence on the rationalization of the life-world. Modernity, liberalism, and the currents of globalization that fuel technical progress can jeopardize the rationalization of our life-world, which is essential for the integrity and solidarity of society, but neglect of technological progress should not be a proposition. Therefore, researchers, with the help of the dialectic of Habermas and Hardiman’s thoughts with their post-secular thoughts, found a motive to examine how Indonesian multiculturalism has the potential to rationalize the development of society. Using the perspective of Jurgen Habermas and Hardiman based on post-secular theory, the purpose of this study helped researchers study the forms of deliberation from the Pela system. Qualitative research is the research method used. The critical paradigm is the chosen solution. This study combines Pela concepts associated with Habermas and Hardiman’s post-secular thinking and uses Habermas’ critical hermeneutic theory. The results of this study show the decision-making process. In this context, the researchers found the Pela concept as the initial capital of the Maluku people to support technical progress without neglecting the roots of solidarity. This research can be a reference for further researchers in sociology, ethnology, and even human resource management.